Validity and clinical utility of the simplified Wells rule for assessing clinical probability for the exclusion of pulmonary embolism - Douma, Renée A.; Gibson, Nadine S.; Gerdes, Victor E. A.; Büller, Harry R.; Wells, Philip S.; Perrier, Arnaud; Gal, Grégoire Le (Thrombosis and Haemostasis, 2009)
The recently introduced simplified Wells rule for the exclusion of pulmonary embolism (PE) assigns only one point to the seven variables of the original Wells rule. This study was performed to independently validate the simplified Wells rule for the exclusion of PE. We retrospectively calculated the prevalence of PE in the “unlikely” probability categories of the original Wells (cut-off ≤4) and the simplified Wells rule (cut-off ≤1) in 922 consecutive patients with clinically suspected PE from a multicenter cohort study. We compared the three-month incidence of venous thromboembolism (VTE) in patients with an unlikely probability and a normal D-dimer test using both scores, and the proportion of patients with this combination (clinical utility). The proportion of patients categorized as PE “unlikely” was similar using the original (78%) and the simplified (70%) Wells rule. The prevalence of PE was 13% (95% confidence interval [CI], 11–16%) and 12% (95%CI, 9.7–15%) for the original Wells and simplified Wells “unlikely” categories, respectively. None of the patients with PE “unlikely” and a normal D-dimer test experienced VTE during three-month follow-up. The proportions of patients in whom further tests could safely be withheld based on PE “unlikely” and a normal D-dimer test was 28% (95%CI, 25–31%) using the original and 26% (95%CI, 24–29%) using the simplified Wells rule. In this external retrospective validation study, the simplified Wells rule appeared to be safe and clinically useful, although prospective validation remains necessary. Simplification of the Wells rule may enhance the applicability.
Keywords: Pulmonary embolism; diagnosis; clinical decision rule; Wells rule; D-dimer